Diferenças no universo futebolístico: a visão de quem torce - Coimbra, Natália dos Reis [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Women's football in Brazil has a great history of fighting prejudice and machismo. For 38 years, women were prohibited from playing sports on Brazilian soil and, only after the repeal of the law in 1983, did women begin their struggles for space within the sports sphere, including within the world of football. Due to so many differences between the modalities, the present study aims to analyze whether there is a difference in the treatment of fans between their respective male and female soccer teams. The method used in this research is qualitative and quantitative, having a descriptive nature, using a questionnaire as a collection instrument. After tabulating and categorizing the collected data, it was seen that 99.1% of the participants support the existence of women's football and that 82% of the participants believe there are differences between male and female games, such as technical differences mentioned by 14% of them. It is understood, through this study, that most fans support women's football and encourage women to go to stadiums, but even with so many progressive speeches, women still face many difficulties to compose the most popular sport in the country.

O futebol feminino no Brasil possui um grande histórico de lutas contra o preconceito e o machismo. Durante 38 anos as mulheres foram proibidas de praticar esportes em solo brasileiro e, somente após a revogação da lei em 1983, as mulheres deram início em suas lutas por espaço dentro do âmbito esportivo, inclusive dentro do universo do futebol. Mediante tantas diferenças entre as modalidades, o presente estudo possui como objetivo analisar se há diferença no tratamento das torcidas entre seus respectivos times de futebol masculinos e femininos. O método utilizado nesta pesquisa é de caráter quali-quantitativo, possuindo natureza descritiva, aplicando um questionário como instrumento de coleta. Após tabulação e categorização dos dados coletados, foi visto que 99,1% dos participantes apoiam a existência do futebol feminino e que 82% dos participantes acreditam haver diferenças entre os jogos masculinos e femininos, como diferenças técnicas que foi citada por 14% deles. É entendido, por meio deste estudo, que grande parte das torcidas apoia o futebol feminino e incentiva a ida das mulheres aos estádios, mas mesmo com tantos discursos progressistas, as mulheres ainda enfrentam muitas dificuldades para compor o esporte mais popular do país.
Differences in the soccer universe: the vision of those who support
Keywords: Soccer; Women; Men; Fans; Differences; Futebol; Mulheres; Homens; Torcida; Diferenças